Advances in Citrus Nutrition 2012
DOI: 10.1007/978-94-007-4171-3_13
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere Microbial Communities: Isolation, Characterization, and Value Addition for Substrate Development

Abstract: Rhizosphere, the soil region nearest to plant root system, inhabits various microorganisms varying in their community structure and diversity, still remains largely unexploited despite so much of breakthroughs in isolation and characterization, but lacks in addressing citrus speci fi c rhizosphere properties. Exploiting microbial synergisms is one of the popular methods of substrate dynamics and associated changes in nutrient environment of rhizosphere. Soil microbial biomass dominates fungal mycelium accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 124 publications
0
4
0
Order By: Relevance
“…and Klebsiella spp., known to improve drought stress (Marasco et al, 2012). For orange trees, Bacillus was the most abundant genus at this time, whereas Bacillus has generally been reported as a dominant genus of the endophytic communities in Citrus (Wu and Srivastava, 2012). In the case of soybean, sampling times corresponded to plant developmental stages (i.e., vegetative, flowering and fruiting, and senescent).…”
Section: Discussionmentioning
confidence: 97%
“…and Klebsiella spp., known to improve drought stress (Marasco et al, 2012). For orange trees, Bacillus was the most abundant genus at this time, whereas Bacillus has generally been reported as a dominant genus of the endophytic communities in Citrus (Wu and Srivastava, 2012). In the case of soybean, sampling times corresponded to plant developmental stages (i.e., vegetative, flowering and fruiting, and senescent).…”
Section: Discussionmentioning
confidence: 97%
“…The bacterial and fungal mix used ( P. fluorescens and P. ochrochloron ) improved the aboveground biomass, as similarly documented for different microbial consortia used in crops, in Citrus sp. [ 36 , 51 , 52 , 53 ], and in the hyperaccumulator Miscanthus × giganteus (Mxg) J.M.Greef, Deuter ex Hodk., Renvoize [ 54 ]. Nevertheless, the documented consortia showed a lower increase in biomass (up to 3.1-fold) compared to our results.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 For example, the ability to culture members of the rhizosphere microbiome from citrus was shown, and known plant growth promoting organisms were isolated, including Bacillus polymyxa, Azotobacter chroococcum, Bacillus mycoides, Pseudomonas fluorescens , and Trichoderma harzianum . 23 In citrus greening disease, or huanglongbing (HLB), the pathogen Candidatus liberibacter spp., was shown to decrease the abundance of these beneficial members of the plant microbiome. 22 , 24 , 25 Blaustein et al also analyzed the leaf microbiome and showed that the Candidatus liberibacter spp.…”
Section: Crop Rhizosphere Microbiomementioning
confidence: 99%